2013
DOI: 10.1007/s11096-013-9902-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of HIV and its treatment among health care providers in South Africa

Abstract: The study shows that both nurses and auxiliary staff are unable to provide the patients with adequate advice about administration of the ARV drugs and management of ADRs. Serious lack of knowledge among HCPs regarding the treatment of HIV presents structural barriers to the patients' adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Since the 1950s, the driving forces of industrial and agricultural development have dramatically decreased the amount of water flowing into the lake, resulting is a reduction in the lake water area from 1000 km 2 to 500 km 2 . As the lake has dried up, the ecological environment of the lake basin has visibly deteriorated [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the 1950s, the driving forces of industrial and agricultural development have dramatically decreased the amount of water flowing into the lake, resulting is a reduction in the lake water area from 1000 km 2 to 500 km 2 . As the lake has dried up, the ecological environment of the lake basin has visibly deteriorated [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Forty‐seven questions in nine papers were on antiretroviral medications for HIV/AIDS . In these papers, it is reported that HCPs lacked knowledge on use of microbicides to prevent HIV and other sexually transmitted diseases, that they were unable to identify medications used for post‐exposure prophylaxis (PEP), and did not know the time point to initiate PEP, duration of treatment and effectiveness of PEP.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven questions in nine papers were on antiretroviral medications for HIV/AIDS [30][31][32][33][34][35][36][37][38]. In these papers, it is reported that HCPs lacked knowledge on use of microbicides Tool (questionnaires) validation: a Self-made with expanded/formal validation process, b Self-made with pretest only, c Cited previous developed tool and used as such, or d Cited previously developed tool with modification, and e Self-made without clear explanation for validation…”
Section: Disease Focusmentioning
confidence: 99%
“…In one such study over three quarters of pharmacy personnel were found to have a poor knowledge on diabetes mellitus management despite the fact that the majority of patients consult with them more than the physicians (Jinqi M, Nansseu JR, Noubiap JJ 2015). Also, from a recent study in Cameroon, Physicians' knowledge towards diabetes evaluation and management was found not to be optimal (Ruud KW, Srinivas SC, Toverud EL 2014). This trend poses a great danger considering the silent nature of DM and also hypertension at their initial stages.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in South Africa evaluating the knowledge of health care providers on HIV and its treatment, Nurses and Auxiliary staff were found to have some basic knowledge about symptoms and mode of transmission of HIV, but great uncertainty was seen regarding treatment with ARV drugs. As much as 39% of the Nurses claimed that nutritious food could also treat HIV disease (Ruud KW, Srinivas SC, Toverud EL 2014). No doubt, good diet is necessary so as to respond to treatment and to supply the minerals that help immunity to build, but treating an ailment that has a causation factor entails either the removal, incapacitation or slowing the replication of such factor as the case may be.…”
Section: Discussionmentioning
confidence: 99%